Engineered 5-HT producing gut probiotic improves gastrointestinal motility and behavior disorder - Li, Bei; Li, Min; Luo, Yanan; Li, Rong; Li, Wei; Liu, Zhi (Frontiers in Cellular and Infection Microbiology, 2022)
Slow transit constipation is an intractable constipation with unknown aetiology and uncertain pathogenesis. Previous studies have found that host 5-hydroxytryptamine (5-HT), an important neurotransmitter, plays essential roles in gut motility. The gut microbiota maintains a symbiotic relationship with the host and has an impact on host metabolism. However, there are scarce data exploiting the effects of gut microbiota-derived 5-HT in constipation-related disease. We genetically engineered the probiotic Escherichia coli Nissle 1917 (EcN-5-HT) for synthesizing 5-HT in situ. The ability of EcN-5-HT to secrete 5-HT in vitro and in vivo was confirmed. Then, we examined the effects of EcN-5-HT on intestinal motility in a loperamide-induced constipation mice model. After two weeks of EcN-5-HT oral gavage, the constipation-related symptoms were relieved and gastrointestinal motility were enhanced. Meanwhile, administration of EcN-5-HT alleviated the constipation related depressive-like behaviors. We also observed increased intestinal microbial diversity and improved microbiota composition during EcN-5-HT treatment. This work suggests that gut microbiota-derived 5-HT might promise a potential therapeutic strategy for constipation and related behavioral disorders.